Feedback of biomechanical information for the elite athlete - Brüggemann, P.; Ae, M.; Smith, R.; Abernethy, B. (1999)
he provision of biomechanical information to elite athletes and their coaches, once the preserve of just a few countries, has become commonplace over the last two decades. In the course of this proliferation, many different systems have been developed for the collection, reduction and analysis of biomechanical data describing, and sometimes explaining, the performances of athletes in a wide range of sports. Much less effort has been directed to the issue of what is done with the results of these exercises in data collection, reduction and analysis. What information should be conveyed to the coach and athlete and how it should be conveyed for best results is thus still largely unknown. This workshop is devoted to a consideration of these issues from the vantage points of scientists who work in biomechanics, physiology and motor control.